Media Alternatif Kacang Merah (Phaseolus vulgaris L) Sebagai Pengganti Media SDA (Sabouraud Dextrose Agar) Untuk Pertumbuhan Jamur Candida albicans - Hardianti, Siti (Deli Medical and Health Science Journal, 2024)
High humidity in Indonesia, which is considered a tropical country, encourages the growth of various types of microorganisms. Fungi are one type of microorganism that thrives in Indonesia. This fungus can infect its host causing a disease known as candidiasis when it grows too quickly in response to physiological changes or decreased immunity. Candida albicans and other fungi are able to thrive on a synthetic medium called Sabouraud Dextrose Agar (SDA) medium. This medium is only available in some locations and is rather expensive. Red kidney beans as an alternative are used to replace SDA media. Fungal growth is aided by the nutrients found in kidney beans. The purpose of this study was to determine whether or not boiled water derived from red beans could be an alternative medium for planting Candida albicans fungi. This kind of descriptive research was conducted in a pre-experimental laboratory observation using the fungus Candida albicans as a parameter and kidney beans as a substrate. Candida albicans fungi can be grown using red bean juice media which is an alternative to SDA media. However, in red bean media, Candida albicans fungi have a smaller size than SDA media. Which is the only macroscopic difference between the two types of fungal colonies. Even so, the small characteristics remain the same. Keywords: Sabouraud dextrose agar (SDA), Red beans, Candida albicans